Pseudokista Pankreas pada Pasien Pediatrik yang Diterapi dengan Drainase Eksternal - Freda S Halim (Medicinus, 2019)
Background : Pseudocyst of pancreas in pediatric patient is a rare case. Therapy usually conservative, while we wait the wall of the pseudocyst become thick and mature, then followed by internal drainage of jejunum and the pseudocyst. The controversy arise in this case where the external drainage is performed due to feeding trouble with significant decrease of the patient’s body weight after trauma. The purpose of this case report is to give insight that external drainage is possible and should be considered in pediatric patient with pseudocyst of pancreas,  primarily  where the exploratory by laparoscopy is possible and feeding problem becomes the main problem.Case : A 4 year old boy come to ER with chief complain pain at the gastric region after blunt abdominal trauma 12 hours before admission. Primary survey was normal with stabile hemodynamic. At first admission, the physician found abdominal distention with tenderness and rebound tenderness without muscular rigidity. In bed-site abdominal USG free fluid was found without abnormality at the solid nor hollow organs.  Abdominal CT showed no active bleeding nor abnormality. After 1 week of inpatient care, feeding (even fluid by oral feeding)becomes a constant problem and abdominal distention is increasing.Therapy : Exploratory by laparoscopic of the abdomen cannot be conducted due to inadequate instruments, then exploratory laparotomy was chosen. Pseudocyst of pancreas was found, 5x4 cm in size with hematoma at the tail of pancreas. External drainage was performed. After the operation the patient dramatically improved, he could tolerate both fluid and solid diet. The patient discharged 4 days after the operation. 3 months after the 1st operation, the patient come with good condition and minimal fluid come from the drain, so the drain was pulled out. Internal drainage was not needed in this case.Conclusion : External drainage could be considered in pediatric patient with pseudocyst of the pancreas if the feeding problem becomes prominent and the laparoscopic instrument is available.